Screening and isolation of amylolytic fungus and crude enzyme characterization from Sago industrial waste - Koh, Seng Fook (Universiti Malaysia Sarawak, UNIMAS, 2007)
Five best amylolytic fungus from 15 successful by isolates from sago industrial waste were selected and studied for crude enzyme starch digesting ability, enzyme properties, enzyme production as well as fungal morphological and molecular identification. This study had revealed that Ceratocystis paradoxa is the best amylolytic fungus from all the isolates. Starch-iodine assay was use to determine the enzyme activity. The kinetic constant (Km), maximum velocity (Vmax) and catalytic constant (kcat) was recorded at 1363.5 mg/ml, 144.9 U/ml, 8.17 mg/ml minutes-1 respectively for Ceratocystis paradoxa. The crude enzyme is thermostable on all assayed temperature where the optimum temperature is 60oC, and maintained high relative activity (80 % and above) in pH 4.0 to 8.0 from studies performed, as well as remaining stable in the presence of metal ions (Cu2+, CO2+, Mn2+, Ca2+, Zn2+, Mg2+, Fe2+) studied. The genetic related study between the 5 isolates via ITS primers and DNA sequencing was also performed. Further study should be emphasizing on the optimization of fungal crude enzyme production, solid state fermentation, cloning of the enzyme expression gene, as well as further molecular studies on the development of expressed sequence tag (EST) and random sequence tags (RSTs) in the future.